GEOGRAPHICAL INFORMATION SYSTEMS IN PORTUGUESE GEOGRAPHY EDUCATION - Maria H. ESTEVES; Jorge ROCHA (European Journal of Geography, 2023)
The use of Geographical Information Systems (GIS) in Geography education is very important in terms of geographical skills development such as spatial literacy, the ability to recognize patterns and relations between geographical phenomena and to explore real-world problems. This paper analyses how Portuguese Geography Education (both in basic and higher education) addresses this important matter and also presents some projects that have been developed in order to enhance the use of GIS in the classroom. Being recognized as an important tool in Geography education the fact remains that a minority of Geography teachers refers using it in their classes for reasons related to lack of training or the need to develop a content centred syllabus in a limited schedule. If learning Geography is about understanding our world, GIS has an important role to play that should be present in Geography Education.